Characterization of serine acetyltransferase (CysE) from methicillin-resistant Staphylococcus aureus and inhibitory effect of two natural products on CysE. (June 2019) - Chen, Changming; Yan, Qiulong; Tao, Mengxing; Shi, Huaying; Han, Xiuyan; Jia, Liqiu; Huang, Yukun; Zhao, Lizhe; Wang, Chao; Ma, Xiaochi; Ma, Yufang
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a major hospital-acquired infective pathogen that has developed resistance to many antibiotics. It is imperious to develop novel anti-MRSA drugs to control the emergence of drug resistance. The biosynthesis of cysteine in bacteria is catalyzed by CysE and CysK. CysE was predicted to be important for bacterial viability, it could be a potential drug target. The serine acetyltransferase activity of CysE was detected and its catalytic properties were also determined. CysE homology model was built to investigate interaction sites between CysE and substrate L-Ser or inhibitors by molecular docking. Docking data showed that residues Asp94 and His95 were essential for serine acetyltransferase activity of CysE, which were confirmed by site-directed mutagenesis. Colorimetric assay was used to screen natural products and six compounds which inhibited CysE activity (IC50 ranging from 29.83 μM to 203.13 μM) were found. Inhibition types of two compounds 4 (11-oxo-ebracteolatanolide B) and 30 ((4 R, 4a R )-dihydroxy-3-hydroxymethyl-7, 7, 10a-trimethyl-2, 4, 4a, 5, 6, 6a, 7, 8, 9, 10, 10a, l0b-dodecahydrophenanthro[3, 2- b ]furan-2-one) on CysE were determined. Compounds 4 and 30 showed inhibitory effect on MRSA growth (MIC at 12.5 μg/ml and 25 μg/ml) and mature biofilm. The established colorimetric assay will facilitate further high-throughput screening of CysE inhibitors from different compound libraries. The compounds 4 and 30 may offer structural basis for developing new anti-MRSA drugs. Highlights: A colorimetric assay was developed to detect the serine acetyltransferase activity of MRSA CysE. Molecular docking analysis showed that Residue Asp94 and His95 were essential for serine acetyltransferase activity of CysE. The colorimetric assay was used to screen natural products and six compounds which inhibited CysE activity were found. Two of these compounds had inhibitory effect on the growth of MRSA and mature biofilm.